Posterior reversible encephalopathy syndrome in cancer patients: experience from a tertiary cancer center, South India - Angadi, Veerendra; Nandennavar, Manjunath; Karpurmath, Shashidhar V.; Jacob, Roshan (International Journal of Research in Medical Sciences, 2019)
Posterior Reversible Encephalopathy Syndrome (PRES) is characterized by seizures, headaches, altered mental status, cortical blindness and typical transient lesions on MRI. PRES may be associated with chemotherapy, molecular targeted drugs and immunosuppressive agents used in patients with cancer. PRES is a very rare condition in cancer patients. PRES is usually reversible with appropriate supportive care and most patients can be restarted with treatment.